Evaluasi Penerapan Audit Mutu Internal Pada STAIN Curup - Hamengkubuwono, Hamengkubuwono (Institut Agama Islam Negeri (IAIN) Curup, 2017)
This study at evaluating the implementation of internal quality audit at STAIN Curup. The data for this study are collected through interview and documentation. Stake or countenance evaluation model is used in this study. Thus, the data analysis involves some following step as: data editing, data coding, tabulating the data, interpreting the data, and drawing conclusion. The result of this study indicates that (1) The Planning internal quality audit is relevant with, attempting to fulfill costumer’s demand, to is relevan with audi vision, audit schedule, the formulation of audit purpose, and the audit form, (2) the implementation of audit is reasonably inappropriate with the purpose and the scope of the audit, and (3) the follow up audit is relevant with the established evaluation standard. As the final thought, this study recommends STAIN Curup conduct well planned and well program internal quality audit continuously so that it can serve as self-reflection for the insitution. Keywords : Evaluation, Internal Quality Audit.